Adults with immune thrombocytopenia who switched to avatrombopag following prior treatment with eltrombopag or romiplostim: A multicentre US study. (18th February 2022) - Al‐Samkari, Hanny; Jiang, Debbie; Gernsheimer, Terry; Liebman, Howard; Lee, Susie; Wojdyla, Matthew; Vredenburg, Michael; Cuker, Adam
Summary: Patients with immune thrombocytopenia (ITP) may respond to one thrombopoietin receptor agonist (TPO‐RA) but not another. Limited data are available describing outcomes in patients who switched from romiplostim or eltrombopag to avatrombopag, a newer oral TPO‐RA. We performed a retrospective observational study of adults with ITP who switched from eltrombopag or romiplostim to avatrombopag at four US tertiary ITP referral centres. Forty‐four patients were included, with a mean ITP duration of 8.3 years and a median (range) of four prior ITP treatments. On avatrombopag, 41/44 patients (93%) achieved a platelet response (≥50 × 10 9 /l) and 38/44 patients (86%) achieved a complete response (≥100 × 10 9 /l). In all patients, the median platelet count on eltrombopag or romiplostim was 45 × 10 9 /l vs 114 × 10 9 /l on avatrombopag ( p  < 0.0001); in patients switched for ineffectiveness of romiplostim/eltrombopag, it was 28 × 10 9 /l on romiplostim/eltrombopag vs 88 × 10 9 /l on avatrombopag ( p  = 0.025). Fifty‐seven percent of patients receiving concomitant ITP medications before switching discontinued them after switching, including 63% of patients receiving chronic corticosteroids. In a heavily pretreated chronic ITP population, avatrombopag was effective following therapy with romiplostim or eltrombopag, with high response rates even in patients with inadequate response to a prior TPO‐RA.